2021
DOI: 10.1021/acsomega.0c05398
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Doping Approach of the Fe–BiOI Microstructure: An Improved Photodegradation Efficiency of Tetracycline

Abstract: The present study describes the strategic doping of Fe metal ions into a BiOI microstructure using ex situ and in situ processes to synthesize a Fe−BiOI microstructure and their effect on photocatalytic degradation of tetracycline (TC). The data suggested that in situ Fe−BiOI (Fe−BiOI-In) has superior performance compared to ex situ Fe−BiOI (Fe−BiOI-Ex) due to the uniform dispersion of Fe within the Fe−BiOI material. Calculated bandgaps ∼1.8, ∼1.5, and 2.4 eV were observed for BiOI (without Fe), Fe−BiOI-In, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Nevertheless, there is an abundant work done on the doping of the metals to the Bi‐Based inorganic semiconductors to augments its photocatalytic activity. The strategic doping of the transition metals in BiOI, Bi 2 WO 6 and BiOBr improves its photocatalytic efficiency such as Fe‐doped BiOI microstructure degrades the tetracycline, [126] Zn 2+ doped BiOI used for the removal of the NO under solar response, [127] ZnO‐BiOI heterostructure to undermine the RhB [128] . However, some of the 3d transition metals such as a Co‐doped Fe 3 O 4 /Bi 2 WO 6 magnetically retrievable photocatalyst for degradation of the contaminants, [129] Ni 2+ /Cu 2+ doped Bi 2 WO 6 nanosheets also enhances the photocatalytic performance [130] and moreover the inner‐transition elements also used for the photocatalytic degradation of 2,4,5‐Trichlorophenoxyacetic using Eu doped Bi 2 WO 6 , [131] Pr 3+ doped Bi 2 WO 6 for RhB degradation for water remediation [132] .…”
Section: Strategies For Advancing Photocatalytic Activity In Bi‐based...mentioning
confidence: 99%
“…Nevertheless, there is an abundant work done on the doping of the metals to the Bi‐Based inorganic semiconductors to augments its photocatalytic activity. The strategic doping of the transition metals in BiOI, Bi 2 WO 6 and BiOBr improves its photocatalytic efficiency such as Fe‐doped BiOI microstructure degrades the tetracycline, [126] Zn 2+ doped BiOI used for the removal of the NO under solar response, [127] ZnO‐BiOI heterostructure to undermine the RhB [128] . However, some of the 3d transition metals such as a Co‐doped Fe 3 O 4 /Bi 2 WO 6 magnetically retrievable photocatalyst for degradation of the contaminants, [129] Ni 2+ /Cu 2+ doped Bi 2 WO 6 nanosheets also enhances the photocatalytic performance [130] and moreover the inner‐transition elements also used for the photocatalytic degradation of 2,4,5‐Trichlorophenoxyacetic using Eu doped Bi 2 WO 6 , [131] Pr 3+ doped Bi 2 WO 6 for RhB degradation for water remediation [132] .…”
Section: Strategies For Advancing Photocatalytic Activity In Bi‐based...mentioning
confidence: 99%
“…The captivated energy helps the electron eject from the valence band. Numerous studies have suggested that the metals and their oxides that efficiently decrease/increase band gap values subsequently improve the performance of the semiconductor materials [52][53][54][55][56][57]. Inorganic dopants are a class of dopants that includes carbon-based nanomaterials (CB-NMs) such as carbon nanotubes (CNTs), carbon nanofibers (CNFs), graphene, GO, and rGO.…”
Section: Strategies To Improve Stabilitymentioning
confidence: 99%
“…Bismuth oxyhalides (BiOXs, X = Cl, Br, and I) are a new family of excellent visible light-responsive photocatalysts characterized by their layered structures interleaved with [Bi 2 O 2 ] 2+ slabs and double X – slabs. This unique structure helps build an internal static electric field between [Bi 2 O 2 ] 2+ and X – , thus improving the separation of photogenerated electron–hole pairs . Among BiOXs, BiOI has attracted considerable interest owing to its relatively narrow band gap compared with BiOCl and broad absorption in the visible-light region. However, practical applications of BiOI-based photocatalysts are still limited because of the high recombination rate of photogenerated electron–hole pairs. , …”
Section: Introductionmentioning
confidence: 99%